You don't; it is false.
For, if n = 0, then log (n + 1) = log 1 = 0, but log n + 1 = log 0 + 1, which is undefined, because no x satisfies e^x = 0.
If you don't like "undefined", then if n = 1, then log (n + 1) = log 2, which is between 0 and 1, since 2 is between 1 and 10. Meanwhile, log n + 1 = log 1 + 1 = 0 + 1 = 1, which is clearly different.
In fact, the only solution to the equation is that of log (n+1) = log n + log 10, or that of log (n+1) = log 10n; you do the rest.
2007-02-01 04:33:39
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
You can't, because it doesn't. Try a quick check: log(5) = 0.69897, log(6) = 0.778151. log(6) does not equal log(5) + 1.
2007-02-01 04:44:46
·
answer #3
·
answered by Grizzly B 3
·
0⤊
1⤋